Pediatric Steroid High-Responder: Irreversible Visual Loss and Secondary Glaucoma Following Chronic Cutaneous-Ocular Dexamethasone Misuse - I Ketut Anom Widyantara Eka Dana Weka Mona; Ni Made Ayu Surasmiati; I Gusti Ayu Ratna Suryaningrum (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Chronic misuse of potent topical corticosteroids can lead to irreversible visual loss, particularly in the pediatric population which exhibits a more aggressive trabecular meshwork remodeling response than adults. This case aims to delineate the silent progression of steroid-induced ocular hypertension in the absence of red-eye symptoms and emphasizes the critical pharmacokinetic risks of cutaneous-ocular absorption in children. Case presentation: We report a catastrophic case of a 7-year-old male presenting with irreversible vision loss following six years of unsupervised, intermittent use of a combined Neomycin-Polymyxin B-Dexamethasone ointment for recurrent hordeolum. The cumulative exposure exceeded 125 mg of Dexamethasone. Examination revealed bilateral dense posterior subcapsular cataracts (PSC) and advanced glaucomatous optic neuropathy in left eye. Following sequential phacoaspiration, the left eye showed persistently elevated IOP (IOP elevated up to 59 mmHg) attributed to decompensated outflow facility. Management required Trabeculectomy with intraoperative 5-Fluorouracil (5 mg/0.1 mL). The high- responder phenotype in children involves rapid formation of Cross-Linked Actin Networks (CLANs) and MYOC gene upregulation. We discuss the double-hit mechanism where cataract extraction washes out hyposecretory factors, unmasking total trabecular blockage. The choice of 5-Fluorouracil over Mitomycin C is defended based on the safety profile regarding hypotony maculopathy in pediatric myopic eyes. Conclusion: Dexamethasone carries a high risk of transcutaneous-ocular absorption in pediatric eye and eyelids. Regulatory reform reclassifying antibiotic-steroid combinations as non-repeatable prescriptions is imperative to prevent such preventable blindness.